Modelado y análisis de temperatura y composición del gas para la evaluación del riesgo de formación de hidratos en gasoductos submarinos (SCIÉNDO INGENIUM, 2026)
Gas hydrates (HGs), also known as clathrates, represent a critical operational threat in natural gas transportation systems in offshore environments, especially under high-pressure, low-temperature conditions. Therefore, a computational framework is presented to assess the risk of hydrate formation in deep-water gas pipelines under offshore operating conditions in Peru. Three Python models are integrated: (1) a predictive tool based on the Towler and Mokhatab correlation, extended to simulate sensitivity to variations in specific gravity; (2) a thermal gradient model calibrated with local oceanographic data, representing the exponential attenuation of temperature with depth; and (3) a compositional adjustment algorithm that transforms multicomponent gas mixtures from a dry to a wet basis, quantifying the impact of water content on hydrate stability. The models are validated with representative field data from Talara, allowing the identification of thermodynamic instability zones and critical compositional thresholds. The results show that mixtures with higher ethane content shift the formation temperature to higher values ​​and provide technical criteria for risk management in subsea pipelines.
Keywords: Offshore operations; Natural gas processing; Hydrate formation; Critical conditions; Simulation_ Python